A novel approach to monitoring and maintenance of industrial PID controllers. (July 2017) - Gao, Xinqing; Shang, Chao; Huang, Dexian; Yang, Fan
Abstract: Due to process nonlinearities and operating condition changes, industrial processes frequently encounter significant dynamics variations, which would compromise the long-term effectiveness of controller monitoring schemes and leads to superfluous alarms. To address these issues, a novel performance benchmark based on the min-max principle is developed for industrial PID controllers, which has satisfactory applicability for nonlinear processes with operating condition switches. Furthermore, a holistic workflow of monitoring and maintenance of industrial PID controllers is proposed, including online identification of process models, poor control detection based on the accessible benchmark, and maintenance guides for poorly behaved controllers. Both simulation and industrial cases studies are presented to demonstrate the effectiveness of the proposed method. Highlights: A min-max principle based benchmark is designed for industrial processes. A controller diagnosis method is proposed based on the closed-loop step response. PID Monitoring and maintenance are integrated in a unified framework. An automated workflow is presented to cope with process dynamic variations.